Occupational Asthma - Mustofa, Syazili; Baladika, Dimas trend Pinaka (Jurnal Kedokteran Universitas Lampung, 2023)
Asthma is a respiratory disease commonly found in general medical practice and in various fields of study. Twenty five percent of adult-onset asthma is occupational asthma. Occupational asthma has become the most prevalent occupational lung disease in developed countries. Allergens that cause occupational asthma are commonly found in work place such as animal proteins, plant proteins, metal transition, chemical substances, etc. Pathogenesis of disease are based on immunologically mediated with participation of specific IgE, immunologically mediated without evidence of participation of IgE and non-immunologic. The diagnosis of occupational asthma does not differ from the diagnosis of general asthma. The difference is that the diagnosis of occupational asthma must be reassured that the exposure to allergens involves a contact to irritating substance within workplace. The best treatment would be to avoid allergens in the workplace. Key words: Occupational asthma (OA), allergens, workplace 1,2